2020
DOI: 10.1155/2020/1592794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Supports’ Positions on the Vibration Characteristics of a Flexible Rotor Shafting

Abstract: In this study, we evaluated the effect of changing supports’ position on the vibration characteristics of a three-support flexible rotor shafting. This dependency was first analyzed using a finite element simulation and then backed up with experimental investigations. By computing a simplified rotor shafting model, we found that the first-order bending vibration in a forward whirl mode is the most relevant deforming mode. Hence, the effect of the supports’ positions on this vibration was intensively investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They pointed out that the oil film dynamic characteristic parameters have time-varying characteristics. Li et al [5] showed that the larger the rotor vortex radius, the stronger the static eccentricity of the damper on the rotor vibration; the larger the static eccentricity of the SFD, the smaller the rotor vibration amplitude (but the risk of nonlinear vibration increases rapidly); when the damper eccentricity ratio is too large, the oil film may be touching, exciting the rotor counter-advancement of the intrinsic frequency; and the vibration amplitude shows violent fluctuations during the phenomenon. Feng et al [6] conducted a comparative experimental study on the vibration damping properties of concentric and non-concentric SFDs.…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that the oil film dynamic characteristic parameters have time-varying characteristics. Li et al [5] showed that the larger the rotor vortex radius, the stronger the static eccentricity of the damper on the rotor vibration; the larger the static eccentricity of the SFD, the smaller the rotor vibration amplitude (but the risk of nonlinear vibration increases rapidly); when the damper eccentricity ratio is too large, the oil film may be touching, exciting the rotor counter-advancement of the intrinsic frequency; and the vibration amplitude shows violent fluctuations during the phenomenon. Feng et al [6] conducted a comparative experimental study on the vibration damping properties of concentric and non-concentric SFDs.…”
Section: Introductionmentioning
confidence: 99%